Calcium Citrate Versus Calcium Carbonate in the Management of Chronic Hypoparathyroidism: A Randomized, Double‐Blind, Crossover Clinical Trial. (24th June 2022) - Naciu, Anda Mihaela; Tabacco, Gaia; Bilezikian, John P; Santonati, Assunta; Bosco, Daniela; Incognito, Giosuè Giordano; Gaspa, Gianluigi; Manfrini, Silvia; Falchetti, Alberto; Trimboli, Pierpaolo; Mazziotti, Gherardo; Napoli, Nicola; et al.
ABSTRACT: In hypoparathyroidism (HypoPT), calcium supplementation is virtually always required, although the disease is likely to be associated with an increased risk of nephrolithiasis. The use of calcium citrate (Ca‐Cit) theoretically could have a positive impact on the nephrolithiasis risk because citrate salts are used to reduce this risk. Our objective was to evaluate the potential therapeutic advantage of Ca‐Cit in comparison with calcium carbonate (CaCO3 ) in HypoPT, on nephrolithiasis risk factors, as well as to their ability to maintain desirable serum calcium levels. We also evaluated these preparations on quality of life (QOL). This randomized, double‐blind, crossover trial recruited 24 adults with postsurgical chronic hypoparathyroidism at Campus Bio‐Medico University of Rome. Participants were randomized 1:1 to Ca‐Cit or CaCO3 for 1 month and then crossed over to the other treatment for another month. The primary outcomes were changes in albumin‐adjusted serum calcium and in ion activity product of calcium oxalate levels (AP[CaOx] index). Secondary efficacy outcomes included changes in SF‐36 survey score, fatigue score, constipation, and adverse events. No difference in terms of AP(CaOx) index was observed between the two groups. However, Ca‐Cit was associated with a significant reduction in the oxalate/creatinine ratio compared with CaCO3 (−2.46 mmol/mol [SD 11.93] versus 7.42 mmol/mol [SD 17.63], p = 0.029). Serum calcium and phosphorus concentration was not different between the two calcium preparations. Ca‐Cit was associated with less constipation ( p = 0.047). No difference was found in QOL scores. Although Ca‐Cit did not modify the AP(CaOx) index when compared with CaCO3, it was associated with a reduction in urinary oxalate excretion that could have a potential beneficial effect on nephrolithiasis risk. These results are likely to have clinical implications in HypoPT, particularly those who do not tolerate CaCO3 and those affected by nephrolithiasis. A longer‐term experience is needed to confirm these findings. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).